Persepsi Guru PJOK terhadap Pembelajaran PJOK Selama Pandemi Covid-19 di Kabupaten Sorong - Harmaman Harmaman; Sugiyono Sugiyono; Leo Pratama (Unimuda Sport Journal : Jurnal Pendidikan Jasmani, 2023)
Some of the phenomena that occurred during the Covid-19 pandemic, including those relating to the corner learning process during the pandemic. This study aims to reveal the perceptions of corner teachers towards the corner learning process during the Covid-19 pandemic in Sorong Regency. This type of research is a qualitative research with descriptive method, using interview, observation, and documentation techniques. The source of the data in this study was the results of interviews with 11 physical education teachers at the elementary school level who were spread across 6 sub-districts in Sorong Regency. Interview data were analyzed using qualitative data analysis with the stages of data reduction, data presentation, and drawing conclusions/data verification. The results showed that there were 4 major themes found in this study, namely, the corner teacher's perception of strengths, weaknesses, readiness, and obstacles in the corner learning process during the Covid-19 pandemic in Sorong Regency.